Examining fraud and determining its level in Iraqi joint stock companies - Talal Mohammed Ali Aljajawy; Ibrahim Naim Al-Aidi (Iraqi Journal for Administrative Sciences, 2024)
It is that fraud and economic and financial social problem take the form of a paralegal based on the intention to deceive third parties to the goals of personal expediency of the problem and increased common with the spread of technological development and globalization of the financial and administrative work and provided the information for the majority of the audience, but that such information mostly incorrect, but has been exploited spread misleading and this led to loss of confidence in the financial statements because they lacked the key characteristics of an appropriate representation and sincere. It is that problem has been reached and based on the recommendations of the professional bodies and international accounting standards and sound foundations and professional ethics and religious to see the level of fraud through the examination and is no doubt that it contributes and effectively in the promotion of confidence to the financial statements, for that was selected sample of companies to determine Mitsui fraud by applying a set of scans fraud measures. The researcher concluded that there is a problem, the proportion of 22% is applicable to the proceedings in Baghdad Company for soft drinks and the percentage of 42.33% is applied in the Bank of Baghdad and that means there are gaps as possible to pass the fraudulent ones, the researcher recommends the need to stay away from cases of fraud and manipulation and deception to other parties through application of rules and accounting procedures correctly, and reduce the flexibility of the laws, regulations, instructions, and requiring workers according to the purpose of the application for him with follow-up enforcement mechanisms. Key words: fraud, fraud examination, Iraqi companies to contribute